POLITISASI RELASI SUAMI-ISTRI: TELAAH KHI PERSPEKTIF GENDER - Durotun Nafisah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
As a positive law, KHI is a political product and full of state nuance. The initiation process through its justification all involveddominant state role. gender bias in KHI exist on Article 79 paragraph 1 about men-wife position, Article 80 paragraph 1- 3 about man’sobligatory, Article 83 paragraph 1 and 2 about wife’s obligatory, also Article 84 paragraph 1 and 2 about nusyuz. Gender inequalitiesfurthermore cause gender injustice that consists of marginalization, stereotype, subordination, double burden, and violence. Gender bias inKHI caused by: first, social-cultural and educational background of every party involved at its formulation. They tend to very patriarchic andphalli-centric. Second, its formulation method only compiled fikih books, appeal study to Middle East, and seminar, without ushul-fikihframework or non-Islamic studies approach